Pretreatment of industrial biosludge to enhance the anaerobic process - Li, Dongzhe (Nanyang Technological University, 2016)
The primary objectives of this study are to enhance treatment of an industrial biosludge with the anaerobic process and to recover as much energy (methane) as is possible. Based on literature review, the rate-limiting factors in the anaerobic treatment of biosludge are dispersion of large biomass particles, rupture of microbial cells, solubilization of feed volatile solids (VS), and decomposition of macromolecular organic matter. Earlier studies have also suggested that ultrasonication and alkaline pretreatment are likely to reduce these rate limitations and, hence, enhance methane generation. However, there are concerns regarding the application of ultrasonication and alkaline pretreatment. Primarily, there is as yet no accurate model to predict the optimal operating parameters for effective ultrasonication. Secondly, the impacts of alkali, ultrasonication, and ultrasonic- alkaline pretreatment on the rate limitations in the anaerobic process have not been compared. Experiments were conducted to determine the optimal feed VS concentrations and ultrasonication amplitudes. The results indicated that high amplitudes improved dispersion of sludge particles and solubilization of both soluble chemical oxygen demand (SCOD) and soluble organic matter (SOC). Hence, the maximum amplitude of 96μm was set in this study. However, the optimal VS concentrations in terms of good particle dispersion and SCOD/SOC solubilization were not necessarily the same. It was determined that 21 g/L was the optimal VS concentration to disperse particulate sludge. However, a higher VS concentration of 31g/L would be more appropriate to solubilize SCOD/SOC. The impacts of low energy ultrasonication, alkali pretreatment, and low energy ultrasonication-alkaline pretreatment on both sludge disintegration and methane generation were compared. The results suggest that the anaerobic treatment of sludge was most affected by solubilization of dissolved organic matter (DOM), decomposition of high molecular weight (HMW) DOM, and rupture of microbial cells. However, dispersion of sludge particles was not a rate-limiting factor for the anaerobic treatment of sludge. Alkaline pretreatment was effective to reduce the rate limitations of the anaerobic process and, hence, enhanced methane generation. As low energy ultrasonication only improved dispersion of the particulate sludge, methane generation could not be enhanced. Ultrasonication-alkaline pretreatment did not perform better than plain alkaline pretreatment in terms of enhancing methane generation. Considering the additional energy consumption by ultrasonication, alkaline pretreatment was therefore pursued in this study. This study provided a clear insight into the composition of alkali-solubilized DOM and its fate in the anaerobic process. The results indicated alkali-solubilized DOM was primarily composed of low molecular weight (LMW) protein-like substances (PL), HMW saccharide-like substances (SL), and humic acid-like substances (HAL). Alkaline pretreatment improved the overall anaerobic degradability of DOM in sludge, while some DOM components (mainly HMW PL and HAL) exhibited low degradability during anaerobic treatment. Alkaline pretreatment led to increase of residual DOM, which was mainly composed of HAL (52.9%) and HMW SL (49.9%). The residual HAL would likely be a degradation byproduct of PL.